Supplemental Role of Fodder Tree Legumes in Dwarf Sheep and Goats Feeding Systems: A Review - Fasae, Oladapo Ayokunle; Adelusi, Felicia Temitope (Agricultura Scientia, 2024)
The potential of fodder tree legumes (FTL) as a promising and nutritional strategy to minimize the problem of insufficient supply of forages, especially during the dry season, in West African dwarf sheep and goats’ production systems was reviewed. For more sustainable agricultural systems, including expanding the use of locally produced available feedstuffs, FTL species with a focus on Leucaena leucocephala, Gliricidia sepium, and Enterolobium cyclocarpum represent an interesting strategy to provide dietary nitrogen and improve feed digestibility, weight gain, and nitrogen retention, thus enhancing dwarf sheep and goats’ productivity. They also contain concentrations of biologically active compounds with nutraceutical value that assist in slowing down the infections with parasitic nematodes of the gastrointestinal tract and mitigating enteric methane emissions from these animals. The dietary crude protein and tannin content ranged from 16.20 to 26.79% and 0.95 to 2.92%, respectively across the FTL species. Mean weight gain (g/day) of 43.23 to 48.59 and 32.46 to 40.87, respectively were reviewed for dwarf sheep and goats fed FTL supplementary diets. Haematological and serum biochemical variables monitored were within the permissible range for healthy animals and showed the adequacy of nutrient supply from FTL species with nutrient utilization to improve productivity. The review concluded that the combination of excellent nutritive value reported for FTL provides important opportunities for sustainable dwarf sheep and goat feeding systems.
Keywords: sheep; goats; tree legumes; tannins; anthelminthic; methane mitigation